Aromatherapy Applications in The Management of The Chemotherapy-Induced Nausea and Vomiting - Nuriye Efe Erturk; Sultan Tasci (Atatürk University, 2021)
Chemotherapy, which is one of the medical treatment methods in coping with cancer, can lead to many problems besides its contribution to the healing process. Nausea-vomiting and retching symptoms in the among these problems are not yet fully controlled despite advances in medical treatment. Inadequate control of chemotherapy-induced nausea and vomiting leads to individuals to complementary and integrative health practices. Of cancer patients, among integrative health care applications that apply in order to battle the symptoms experienced in the with cancer and treatment process are applications as phytotherapy-herbal product use, relaxation exercises, hypnosis, acupuncture, acupressure, massage and music therapy. Aromatherapy which under phytotherapy is a application that is the used of essential oils produced from nice smelling parts of plants by patients in order to treat or to relieve physical and emotional symptoms.